Functional and clinical consequences of changes to natural killer cell phenotypes driven by chronic cytomegalovirus infections - Lee, S.; Doualeh, M.; Affandi, Jacquita; Makwana, N.; Irish, A.; Price, Patricia (WILEY-LISS, 2019)
Cytomegalovirus (CMV) infections may affect natural killer (NK) cells and are implicated in age-related disorders—notably poor vascular endothelial function. Changes may be greater in renal transplant recipients (RTR) as they have a high burden of CMV and may influence antibody-dependent cellular cytotoxicity (ADCC) responses to viral antigen. We obtained blood mononuclear cells from RTR stable after transplantation (n = 27) and age- and sex-matched controls (n = 28). Natural killer (NK) cells were assessed for expression of CD107a or TNF-a, after stimulation with autologous antibodies bound to CMV glycoprotein B (measuring ADCC) or anti-CD16 (measuring NK cell activation). Alleles of FCRG3A (encoding CD16; rs396991) were determined by the Taqman assay. The vascular endothelial function was assessed using flow-mediated dilatation (FMD) of the brachial artery. Proportions of NK cells expressing CD16 ex vivo were lower in RTR. Frequencies of NK cells expressing NKG2C or LIR-1 or lacking FcR? were highest in CMV-seropositive RTR. ADCC was affected by rs396991 genotype and CMV gB antibody levels, but not by RTR status or detection of CMV DNA in plasma. Responses of FcR?-NK cells to anti-CD16 were lower compared to FcR?+ NK cells. Increased percentages of LIR-1 + and FcR?- NK cells correlated with lower FMD. In summary, CMV evokes substantial and similar ADCC responses in CMV seropositive RTR and controls. The equivalence may reflect higher titers of CMV reactive antibody in RTR, as NK responses stimulated by ligation of CD16 were lower. NK cells that were LIR-1 + and/or FcR?- were induced by CMV and correlated inversely with vascular endothelial function.